2006
DOI: 10.1080/09593332708618714
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Drying Conditions ofSargassumsp. Alga on the Bioadsorption of Hexavalent Chromium

Abstract: Industrial wastes containing synthetic organic compounds and heavy metals are among the most dangerous residues, whose growth has followed the increase in industrial activity. Heavy metals are readily assimilated into the food chain and therefore easily accumulated in the ecosystem. To remove heavy metals from aqueous solutions, marine algae may be used as adsorbents either in their natural form or after treatments by a cross-linking process to improve their mechanical resistance. Drying of biosorbents, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The biosorption capability of algae has been attributed mainly to the cell wall, which is composed of reticular apparatus by polysaccharides, protein, and lipids. There are several chemical groups can attract and sequester the metals: carbonyl, hydroxyl, carboxyl, amino, amido, sulfhydryl, and phosphate, of which the carboxyl and sulfhydryl groups are considered to play an important role in binding (Rocha, De Assis, Da Silva, & Gonçalves, ).The sorption capacity of different kinds of algae is distinct, which can be attributed to the chemical composition of the corresponding cell walls.…”
Section: Introductionmentioning
confidence: 99%
“…The biosorption capability of algae has been attributed mainly to the cell wall, which is composed of reticular apparatus by polysaccharides, protein, and lipids. There are several chemical groups can attract and sequester the metals: carbonyl, hydroxyl, carboxyl, amino, amido, sulfhydryl, and phosphate, of which the carboxyl and sulfhydryl groups are considered to play an important role in binding (Rocha, De Assis, Da Silva, & Gonçalves, ).The sorption capacity of different kinds of algae is distinct, which can be attributed to the chemical composition of the corresponding cell walls.…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have reported increases in the metal sorption capacity in the case of heat-inactivated biomass samples (Kacar et al 2002;Bayramoglu, Bektas, and Arica 2003;Gurisik et al 2004;Arica et al 2005;Tunali, Kiran, and Akar 2005). Drying of biomass also has been reported by many researchers as having a positive effect on metal uptake (Rocha et al 2006). On the other side, it seems likely that saponification of various ester groups may be involved, increasing the number of carboxylate groups on the treated surfaces (Reddad et al 2002;Xuan et al 2006;Li et al 2007;.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, drying and grinding biomasses reveal the sites where metal ions could be sequestered and so increase the probability of encountering metal ions. Besides, the metal removal system using dried biomass is not subject to toxicity limitations (Rocha et al, 2006, Parameswari et al, 2009and Mane et al, 2010.…”
Section: Introductionmentioning
confidence: 99%